Therapeutic and Reconstructive Management: Addressing Neglected Squamous Cell Carcinoma - Catalin Gheorghe BEJINARIU; Vladimir Aurelian ENACHESCU; Irina Mihaela ZAHARIA (Modern Medicine)
This paper presents the therapeutic approach for a patient hospitalized for the treatment of squamous cell carcinoma located in the left frontal region. The patient’s medical history was marked by multiple surgical interventions that resulted in tumor recurrence. The therapeutic protocol included the excision of the tumor while respecting oncological safety margins, followed by reconstruction using a local frontal flap for the coverage of the remaining soft tissue defect. Histopathological examination confirmed the radical excision. Following the specific surgical therapy, the patient’s recovery went well. After the surgical intervention, the patient was able to continue the psychiatric treatment, for the treatment of the psychiatric pathology accentuated by the unfavorable clinical context of the last 2 years.